Herbes à vendre: les dits de l’Herberie de Rutebeuf et de ses continuateurs - Alain Corbellari (Studia Romanica Posnaniensia, 2025)
Rutebeuf’s Dit de l’Herberie, curiously constructed in two parts, one in verse, the other in prose (it’s Rutebeuf’s only prose text), seems to have prompted two imitations (unless he himself drew inspiration from one of the other two texts). This is a “mini-genre” that can be attached to the more extensive “professional dits” series, and which raises questions about urban representations in the central Middle Ages: an affectation of “realism”? Pure puerility with obscene undertones? Or a piece that paradoxically serves to build the self-confidence of the juggler Rutebeuf? We’ll take each of these paths in turn.